LITERATURE REVIEW STUDY: DETERMINANTS OF THE OCCURRENCE OF DIABETIC RETINOPATHY IN TYPE 2 DIABETES MELLITUS PATIENTS - Suriyanto, Suriyanto; Abd Hamid , Abdul Alif (Lux Mensana: Journal of Scientific Health, 2024)
Introductio: Diabetic retinopathy (RD) ranks 4th as a cause of blindness globally aftercataracts, glaucoma and macular degeneration. Blindness due to RD is a health problembecause it will reduce a person's quality of life and decrease productivity, causing a socialburden on society. Globally, around 95 million DM patients experience diabeticretinopathy (35.4%) of which one third are at risk of losing their vision and more than 75%of diabetes sufferers will experience diabetic retinopathy 20 years after diagnosis.Methods: The method used in this writing is literature study which aims to compile,tabulate and compare research results. Articles were collected via the PubMed andMendeley search engines. The keywords used are diabetic retinopathy and diabetesmellitus. The articles went through an elimination and filtering process with the resultsbeing 14 articles according to the research topic. Result & Analysis: Results from a fulltext review of 14 journals containing at least 1 RD factor and in accordance with theinclusion and exclusion criteria. From the 14 articles reviewed, the risk factors were age(87.5%), hypertension (77.8%), duration/length of suffering from DM (76.9%) and HbA1clevels (87.5%), these four factors stated there is a significant relationship with theoccurrence of RD in type 2 DM patients. Discussion : Based on the results of the study, itwas concluded that most journals stated that there was a relationship between the factorsage, hypertension, duration of DM and HbA1c levels on the incidence of RD in type 2 DMpatients.